On perspective errors in endoscopic PIV - Reeves, Mark; Lawson, Nicholas J. (Elsevier, 2004)
Results are presented from a single and dual lens endoscopic PIV imaging system with a view to application of PIV where optical access is restricted such as internal flows. The dual lens PIV images were processed using cross-correlation, a cubic mapping function and standard stereoscopic relationships. For the single lens system, the images were processed using cross-correlation and a quadratic distortion-mapping function. Results have shown the single lens system to have in-plane errors an order of magnitude greater than the stereoscopic dual lens endoscopic PIV system. These errors are generated by perspective effects. Use of the stereo arrangement is therefore recommended wherever quantitative 3D velocimetry data is acquired using an endoscopic system.
Keywords: Signal processing; Stereoscopic PIV; Endoscope; Perspective errors